2019
DOI: 10.1634/theoncologist.2018-0672
|View full text |Cite
|
Sign up to set email alerts
|

Value of Tumor Growth Rate (TGR) as an Early Biomarker Predictor of Patients’ Outcome in Neuroendocrine Tumors (NET)—The GREPONET Study

Abstract: Introduction Tumor growth rate (TGR; percent size change per month [%/m]) is postulated to be an early radiological biomarker to overcome limitations of RECIST. This study aimed to assess the impact of TGR in neuroendocrine tumors (NETs) and potential clinical and therapeutic applications. Materials and Methods Patients (pts) with advanced grade (G) 1/2 NETs from the pancreas or small bowel initiating systemic treatment (ST) or watch and wait (WW) were eligible. Baseline and follow‐up scans were retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(81 citation statements)
references
References 20 publications
(26 reference statements)
8
67
3
Order By: Relevance
“…Analyses derived from the prospective randomized CLARINET study showed that pretreatment TGR was able to predict response to Lanreotide in terms of progression-free survival in patients with NET. 31 The multicentric retrospective GREPONET study, 32 including metastatic NET patients, confirmed these results, supporting the role of pretreatment TGR as a possible predictive factor for tumor response. We hypothesized that TGR could also be a helpful predictor of patient outcome with future utility for treatment decision making and better understanding of HCC biological behavior.…”
Section: Discussionmentioning
confidence: 64%
“…Analyses derived from the prospective randomized CLARINET study showed that pretreatment TGR was able to predict response to Lanreotide in terms of progression-free survival in patients with NET. 31 The multicentric retrospective GREPONET study, 32 including metastatic NET patients, confirmed these results, supporting the role of pretreatment TGR as a possible predictive factor for tumor response. We hypothesized that TGR could also be a helpful predictor of patient outcome with future utility for treatment decision making and better understanding of HCC biological behavior.…”
Section: Discussionmentioning
confidence: 64%
“…A post hoc analysis from a phase II study revealed that higher pretreatment TGR tended to be associated with shorter PFS in grade 1 or 2 gastroenteropancreatic neuroendocrine tumors (GEP-NETs) receiving lanreotide (27), and the CLARINET study further validated this finding (18). A TGR 0 < 4%/m predicted inferior PFS in G1 or G2 NET patients regardless of treatment modalities (21). Similarly, patients with higher pre-treatment tumor growth rate--measured as specific growth rate (SGR) experienced worse PFS in locally advanced NSCLC undergoing definitive chemoradiation therapy (CRT) (28).…”
Section: Discussionmentioning
confidence: 91%
“…Tumor growth rate (TGR) provides quantitative assessment of change in tumor volume over time according to RECISTdefined sum of the longest diameters of the target lesions (SLD) from two computed tomography (CT) scans and time interval between them (17). Previous studies have showed that TGR was correlated with treatment response or clinical outcomes in patients with neuroendocrine carcinoma, renal cell carcinoma, or hepatocellular carcinoma treated with angiogenesis inhibitors or transarterial chemoembolization (18)(19)(20)(21)(22)(23). These findings suggested that TGR could serve as an early radiological biomarker to predict patient's survival outcomes and to tailor radiological follow-up strategies and patients' management.…”
Section: Introductionmentioning
confidence: 99%
“…Combining different imaging technologies and assessment of disease with cross-sectional and molecular imaging is increasingly relevant for patients with PanNETs, not only for treatment selection following a theranostic approach, but also for assessment of response to therapy [143,144]. The development of novel radiological assessment strategies may also be of help (i.e., alternative cut-off definitions for assessment of response [145] or assessment of Tumour Growth Rate (TGR) [123,146,147].…”
Section: Ongoing Challengesmentioning
confidence: 99%